TNF+ regulatory T cells regulate the stemness of gastric cancer cells through the IL13/STAT3 pathway - Zhao, Rou; Cao, Guanjie; Zhang, Baogui; Wei, Li; Zhang, Xiaobei; Jin, Meng; He, Baoyu; Zhang, Bin; He, Zhun; Bie, Qingli (Frontiers in Oncology, 2023)
Regulatory T cells (Tregs) are an important component of the tumor microenvironment; however, the interaction between Tregs and gastric cancer cells is not completely understood. Recent studies have shown that Tregs participate in cancer cell stemness maintenance. In this study, we performed single-cell RNA sequencing of gastric cancer and adjacent tissues and found that Tregs with high TNF expression were recruited to gastric cancer tissues and were significantly correlated with patient survival. TNF+ Tregs significantly contribute to tumor growth and progression. Our studies have further demonstrated that TNF+ Tregs promote the stemness of gastric cancer cells through the IL13/STAT3 pathway. Therefore, blocking the interaction between TNF+ Tregs and gastric cancer cells may be a new approach in the treatment of gastric cancer.